Distribution and covering percentage of sponge (Porifera) in different coral reef condition and depth in Barranglompo Island, South Sulawesi (Biodiversitas Journal of Biological Diversity, 2008)
In 1996, four specieses of sponge namely Auletta sp., Callyspongia pseudoreticulata, Callyspongia sp., and Halichondria sp. have been potentially identified as bacteriside for fishery commodities. Nevertheless, information on sponge distribution, its covering percentage, and its habitate are still very little. Observation on distribution and abundance of sponge was conducted in the Southeastern and theNorthwestern part of Barranglompo Island, South Sulawesi, using scuba diving set and under water writting tools. At first, coral reef condition in 3 and 10 m depths up to 100 m length of shore line were observed in both stations, using â€œlifeform methodâ€. Then distribution and covering percentage of sponge, biotic and abiotic factor in 3, 6, 9, and 12 m depths in both stations were examined using â€œsquare transect methodâ€. The result showed that different coral reef condition qualitatively causes different of sponge species distribution, but quantitatively not significantly different (P>0,05) on its covering percentage. It was also found that generally sponge grows better at thedead coral where no other biotic organism around.Â© 2008 Jurusan Biologi FMIPA UNS SurakartaKey word: distribution, covering percetage, sponge, habitat, Barranglompo Island